A Giant 3d‐4f Polyoxometalate Super‐Tetrahedron with High Proton Conductivity. Issue 3 (3rd November 2020) - Li, Shu‐Rong; Wang, Hai‐Ying; Su, Hai‐Feng; Chen, Hui‐Jun; Du, Ming‐Hao; Long, La‐Sheng; Kong, Xiang‐Jian; Zheng, Lan‐Sun
Abstract: The assembly of gigantic heterometallic metal clusters remains a great challenge for synthetic chemistry. Herein, based on the slow release strategy of lanthanide ions and in situ formation of lacunary polyoxometalates, two giant 3d‐4f polyoxometalate inorganic clusters [LaNi12 W35 Sb3 P3 O139 (OH)6 ] 23− (LaNi12 ) and [La10 Ni48 W140 Sb16 P12 O568 (OH)24 (H2 O)20 ] 86− (La10 Ni48 ) are obtained. The nanoscopic inorganic cluster La10 Ni48 possesses a super tetrahedron structure, which can be viewed as assembly from four LaNi12 molecules encapsulating a central [La6 (SbO3 )4 (H2 O)20 ] 6+ octahedron core. This giant aesthetic La10 Ni48 tetrahedron containing 214 metal ions is the largest 3d‐4f cluster reported thus far in polyoxometalate system. More interestingly, the LaNi12 and La10 Ni48 display high stability in solution and La10 Ni48 displays excellent proton conductivity. Abstract : Two giant heterometallic 3d‐4f polyoxometalate inorganic clusters LaNi12 and La10 Ni48 are obtained based on the slow release strategy of lanthanide ions. This giant La10 Ni48 tetrahedron containing 214 metal ions is the largest 3d‐4f cluster reported thus far in polyoxometalate system. More interestingly, the LaNi12 and La10 Ni48 display high stability in solution and La10 Ni48 displays excellent proton conductivity.